Comparison of three models for winter wheat yield prediction based on UAV hyperspectral images - Xu, Xiaobin; Teng, Cong; Zhu, Hongchun; Feng, Haikuan; Zhao, Yu; Li, Zhenhai (International Journal of Agricultural and Biological Engineering, 2024)
Predicting crop yield timely can considerably accelerate agricultural production management and food policy-making, which are also important requirements for precise agricultural development. Given the development of hyperspectral imaging technology, a simple and efficient modeling method is convenient for predicting crop yield by using airborne hyperspectral images. In this study, the Unmanned Aerial Vehicle (UAV) hyperspectral and maturity yield data in 2014-2015 and 2017-2018 were collected. The winter wheat yield prediction model was established by optimizing Vegetation Indices (VIs) feature scales and sample scales, incorporating Partial Least Squares Regression (PLSR), Random Forest algorithm (RF), and Back Propagation Neural Network algorithm (BPN). Results showed that PLSR stands out as the optimal wheat yield prediction model considering stability and accuracy (RMSE=948.88 kg/hm2). Contrary to the belief that more input features result in higher accuracy, PLSR, RF, and BPN models performed best when trained with the top 3, 8, and 4 VIs with the highest correlation, respectively. With an increase in training samples, model accuracy improves, reaching stability when the training samples reach 70. Using PLSR and optimal feature scales, UAV yield prediction maps were generated, holding significant value for field management in precision agriculture. Key words: hyperspectral imagery, unmanned aerial vehicle, winter wheat, yield prediction model, remote sensing DOI: 10.25165/j.ijabe.20241702.5869 Citation: Xu X B, Teng C, Zhu H C, Feng H K, Zhao Y, Li Z H. Comparison of three models for winter wheat yield predictionbased on UAV hyperspectral images. Int J Agric & Biol Eng, 2024; 17(2): 260–267.